Evaluation of the Antibacterial and Antifungal Potential of Peltophorum africanum: Toxicological Effect on Human Chang Liver Cell Line - Benjamin I. Okeleye; Noxolo T. Mkwetshana; Roland N. Ndip (The Scientific World Journal, 2013)
We assessed the in vitro antimicrobial activity of Peltophorum africanum by means of the agar well and macrodilution methods. The toxicity on a normal human liver cell (Chang liver cell) was determined using the CellTiter-Blue cell viability assay, and the compounds contained in the fractions were identified using GC-MS. Zone diameter of inhibition of the extract ranged from 12.5±0.7  to  32 ± 2.8 mm for bacteria and from  7.5 ± 0.7  to  26.4 ± 3.4 mm for yeast. Marked activity of the extract was observed against Plesiomonas shigelloides ATCC 51903, with MIC and MLC values of 0.15625 and 0.3125 mg/mL, respectively. The extract was both bactericidal (MICindex≤2) and bacteriostatic/fungistatic (MICindex>2) in activity. Lethal dose at 50 (LD50) showed 82.64±1.40 degree of toxicity at 24 hrs, and 95 percentile of cell death dose activity ranged from log 3.12±0.01  to  4.59±0.03. The activity of the eight fractions tested ranged from 1.0±0.5  to  3.7±1.6 mg/mL (IC50) and from  2.1±0.8  to  6.25±0 mg/mL (IC90). The extract was toxic to human Chang liver cell lines.